The Effect of Digital Flipbook on the Behavior of Using Light Fire Extinguisher in X Hospital Workers - Nadiyah Hanun Afifah; Marji Marji; Erianto Fanani; Supriyadi Supriyadi (Universitas Negeri Malang, 2024)
Based on data from the Indonesian National Police, there were 5,336 fire cases from May 2018 to July 2023. In October 2021 Hospital X experienced a fire in the Pharmacy Building. The easiest fire protection tool to use is light fire extinguisher. In order for workers to understand the use of light fire extinguisher, it is necessary to carry out training. Light fire extinguisher training can be carried out by providing digital flipbooks via WhatsApp. This study aims to determine the effect of digital flipbooks on fire extinguisher use behavior in X Hospital workers. The research method is True Experiment Design. The sample in this study were 44 workers and used total sampling. Data analysis in this study using the independent T test and Mann Whitney Test which obtained a Sig value. 0.000 less than 0.05 which means that there is an influence of digital flipbooks on knowledge, attitudes, and skills in the use of fire extinguishers. It is hoped that light fire extinguisher training will be carried out evenly to every worker in the hospital, if a fire occurs workers can extinguish the fire using light fire extinguisher.